IMPLEMENTASI PROSES PEMBELAJARAN PRAKTIK LABORATORIUM MATA KULIAH ASUHAN KEBIDANAN I ( KEHAMILAN ) MAHASISWA SEMESTER II PROGRAM STUDI D-III KEBIDANAN SEKOLAH TINGGI ILMU KESEHATAN HUSADA JOMBANG - Ardiyanti Hidayah; Samsi Haryanto; Sri Jutmini (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
This study aims to determine (1) Learning Laboratory Practice Pregnancy Care Prodi D-III Midwifery STIKES Husada Jombang include (a) Laboratory Practice Learning Process; (B) Laboratory Learning Methods; (C) Schedule Settings; (D) Infrastructures; (E) Evaluation and Achievement System. (2) Constraints and How to Resolve. This study used descriptive qualitative approach to explore as much as possible the facts in accordance with the focus of research. Techniques of collecting data through interviews, observation and documentation involving program managers, coaches and student education level II Prodi D- III Midwifery STIKES Husada Jombang. Data were analyzed using constant comparison method. The validity of the data obtained by the extension of research time, perseverance observation, continuous engagement, triangulation and reviews of key informants. Triangulation used include triangulation of sources, methods and timing. The results of the study explained that the lesson preparation of midwifery laboratory practice about pregnancy care in Prodi D-III Midwifery STIKES Husada Jombang do several steps: (a) Preparation of schedule based on the syllabus (b) Strategies and Learning Methods using laboratory methods together (d) Evaluation study with response , assessment of affective, cognitive assessment and psychomotor assessment using the checklist. conclusion; In practice assessment, the aspects that include skills, attitudes and mastery of the material to assess indicators of the activities carried out in the laboratory based on the existing competence in the form of a checklist